Educação e trabalho : a formação do jovem trabalhador no Brasil e em Portugal a partir da década de 1990 - Fagiani, Cílson César (2016)
The aim of the study was to analyze the relationship between work and education with a focus on problematic of formation of young worker in the context of neoliberal policies, policies that emphasize training for the labor market, particularly from the 1990s in Brazil and Portugal. Part of this thesis was developed in Portugal, in the modality of doctoral sandwich, supported by CAPES. Was taken as the object of analysis the educational policies implemented by both governments, from a historical review of the structural transformations of capitalism and its dialectical relation to the forms of technical organization of the production process. The hypothesis that guided the research was that the Brazilian and Portuguese governments saved their historicaleconomic and cultural characteristics of each country, are implementing educational policies and reforms that favor a focused educational training to meet the needs of the labor market, discouraging and even inhibiting critical education, which enables the formation of a social subject know themselves and socio-cultural relations that surround it. Both the Portuguese situation as in Brazil were analyzed as the primary source of research official documents released by government agencies, official data released by the education authorized bodies and data released by the press. As a result there is the permanence of the capitalist system class structure via maintaining a dual educational system, namely: education for the working class and another for the bourgeois class. The results and conclusions presented show that the educational reforms tend to form primarily to meet specific demands of the labor market, which change rapidly due to technological innovations.